Preoperative care of the newborn with myelomeningocele - (:unkn) unknown (Springer Milan, 2008)
Children with spina bifida comprise one of the largest groups of patients for whom pediatric neurosurgeons care. Management of these children is extraordinarily complex and may require the integrated efforts of caregivers from many disciplines. © 2008 Springer-Verlag Italia.